2023
DOI: 10.3390/biom13091427
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers and Imaging Indices for the “Vulnerable Patient” with Carotid Stenosis: A Single-Center Study

Nikolaos Kadoglou,
Konstantinos G. Moulakakis,
George Mantas
et al.

Abstract: Background: We investigated the relationship of matrix metalloproteinases (MMPs), cardio-ankle vascular index (CAVI), and Gray-Scale Median (GSM) score with the severity and vulnerability of carotid atherosclerosis and major adverse cardiovascular events (MACE) during follow-up of carotid artery revascularization. Methods: We enrolled 262 patients undergoing carotid revascularization therapy (GRT), 109 asymptomatic patients with low-grade carotid stenosis (40–70%) receiving conservative treatment (GCT), and 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Besides CRP, novel biomarkers like matrix metalloproteinases (MMPs) 3,7, and 9 and the tissue inhibitors of metalloproteinase (TIMP)-1 are elevated in those with carotid atherosclerosis, and the elevation of those biomarkers parallel with the percentage of carotid artery stenosis. Patients with elevated TIMP-1, MMP-3, MMP-7, and MMP-9 more often require carotid revascularization than those without carotid artery stenosis or those under conservative treatment [ 45 ]. The early detection of the inflammation and calcification at the molecular level in bilateral carotid artery atherosclerosis was recently detected using positron emission tomography/computed tomography (PET/CT) with (18F) sodium fluoride (NaF) as a tracer.…”
Section: Discussionmentioning
confidence: 99%
“…Besides CRP, novel biomarkers like matrix metalloproteinases (MMPs) 3,7, and 9 and the tissue inhibitors of metalloproteinase (TIMP)-1 are elevated in those with carotid atherosclerosis, and the elevation of those biomarkers parallel with the percentage of carotid artery stenosis. Patients with elevated TIMP-1, MMP-3, MMP-7, and MMP-9 more often require carotid revascularization than those without carotid artery stenosis or those under conservative treatment [ 45 ]. The early detection of the inflammation and calcification at the molecular level in bilateral carotid artery atherosclerosis was recently detected using positron emission tomography/computed tomography (PET/CT) with (18F) sodium fluoride (NaF) as a tracer.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prognostic utility of CAVI in SLE patients, its employment for cardiovascular risk stratification could revolutionize patients' management by endorsing more aggressive therapeutic approaches in otherwise uncomplicated SLE patients. Numerous studies have demonstrated the association of CAVI with the development of cardiovascular events in patients with established atherosclerotic CVDs (ASCVDs) [33,34] or those at high risk for ASCVDs [35]. No data are available for the prognostic value of CAVI in the SLE population and this remains to be proved.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prognostic utility of CAVI in SLE patients, its employment for cardiovascular risk stratification could revolutionize patients' management by endorsing more aggressive therapeutic approaches in otherwise uncomplicated SLE patients. Numerous studies have demonstrated the association of CAVI with the development of cardiovascular events in patients with established atherosclerotic CVDs (ASCVDs) [29,30] or those at high risk for ASCVDs [31]. No data are available for the prognostic value of CAVI in SLE population and this remains to be proved.…”
Section: Discussionmentioning
confidence: 99%